Pharmacological Investigation of Asphodelus tenuifolius Cav. for its Potential Against Thrombosis in Experimental Models. Issue 3 (15th September 2022) - Gul, Humaira; Jamshed, Ayesha; Jabeen, Qaiser
Background: Thrombosis is a major disorder which is an outcome of an imbalance in the hemostatic system that develop undesirable blood clot and hinder blood circulation. Purpose: The current study was designed to verify the potential of aqueous methanolic crude extract of Asphodelus tenuifolius Cav . (At.Cr), used traditionally as remedy in circulatory problems. Research Design: Antioxidant activity, FTIR, and HPLC analysis were performed. In-vitro clot lysis assay was performed on human blood samples, and in-vivo acute pulmonary thromboembolism model was developed by administering the mixture of collagen and epinephrine in tail vein of mice. Carrageenan-induced thrombosis and FeCl3 -induced carotid arterial thrombosis models were developed in rats. Results: At.Cr demonstrated significant increase in lysis of human blood clot. Bleeding and clotting times were increased dose-dependently. Lungs histology showed clear alveolar spaces with decreased red blood cells congestion. Reduction in infarcted tail length, augmentation in prothrombin time, and activated partial thromboplastin time with decrease in platelet count were observed. At.Cr also prolonged the arterial occlusion time and reduced the weight of thrombus and TXB2 levels dose-dependently. Conclusions: The results demonstrated the antithrombotic and thrombolytic potential of At.Cr due to activation of coagulation factors through extrinsic and intrinsic pathways.